Textbook of surgery - Tjandra, Joe J. (Joe Janwar); Clunie, Gordon J. A.; Kaye, Andrew H.; Smith, Julian A. (Blackwell Pub., 2006)
Core book for medical and surgical students providing a comprehensive overview of general and speciality surgery. Each topic is written by an expert in the field. The book focuses on the principles and techniques of surgical management of common diseases. Emphasis is placed on problem-solving to guide students and junior doctors through their surgical training. Throughout the book are numerous reproducible line.